Effects of Sn doping on the optoelectronic properties of reactively evaporated In4Se3 thin films. (1st August 2019) - Anuroop, R.; Pradeep, B.
Abstract: Polycrystalline In4 Se3 : Sn thin films are prepared on glass substrate by reactive evaporation under a vacuum of 10 −5 mbar. The characterizations of the samples are done using XRD, FESEM, XPS and UV-Vis-NIR spectrophotometer. The optical band gap shift of the sample, above the carrier concentration of 1.833 × 10 17 cm −3, is well described by Burstein-Moss model. The resistivity of the samples is found to decrease as a result of Sn incorporation. Our results show that in all samples, impurity scattering and lattice vibration scattering are the main factors affecting the electrical properties. Photoconductivity studies at room temperature show that visible photoresponsivity of the films increases with increase in Sn concentration. These improvements in optoelectronic properties facilitate the usefulness of such films in device applications.